Intraocular Pressure Response to Moderate Exercise during 30-Min Recovery - Najmanova, Eliska; Pluhacek, Frantisek; Botek, Michal (Optometry and vision science, 2016)
PURPOSE: The aim of the study was to evaluate intraocular pressure (IOP) before and after moderate exercise in normal healthy individuals with defined physical exertion. The second aim of this investigation was to determine the correlation between resting IOP (IOPr) and its change induced by exercise as well as the relationship between resting heart rate (HRr) and changes in IOP after exercise. METHODS: Forty-one healthy volunteers between the ages of 19 and 25 years were recruited for the study. First, the resting (reference) values IOPr and HRr were measured after 30 min of resting time. Volunteers consequently performed 30 min of exercise on a bicycle ergometer. Intraocular pressure was remeasured immediately after the end of exercise (the relevant IOP change was denoted as ΔIOP0) and subsequently repeated 5, 10, 20, and 30 min after exercise. RESULTS: A significant decrease in IOP compared with the resting value (post hoc Tukey honest significant difference test) was found immediately after exercise (p = 2 × 10) and 5 and 10 min after exercise (p = 2 × 10 and p = 3 × 10). Significant relationships were found between the change in IOP (ΔIOP0) and baseline IOP (IOPr) and between the baseline resting heart rate (HRr) and the change in IOP (ΔIOP0). CONCLUSIONS: There was a significant IOP-lowering effect, which was persistent for 10 min after 30 min of exercise. The IOP change was dependent on the initial IOP reading and initial HR.
Keywords: zátěžový test; Humans; Female; mladý dospělý; dospělí; Heart Rate; lidé; obnova funkce; Exercise Test; nitrooční tlak; Tonometry, Ocular; Adult; ženské pohlaví; tonometrie oční; Male; srdeční frekvence; Recovery of Function; Young Adult; Exercise; mužské pohlaví; cvičení; Intraocular Pressure